Corylus avellana: A Source of Diarylheptanoids With α-Glucosidase Inhibitory Activity Evaluated by in vitro and in silico Studies - Masullo, Milena; Lauro, Gianluigi; Cerulli, Antonietta; Bifulco, Giuseppe; Piacente, Sonia (Frontiers in Plant Science, 2022)
Corylus avellana hard shells, green leafy involucres, leaves, and male flowers have shown to be a source of diarylheptanoids, a class of natural products with promising biological activities. Cyclic diarylheptanoids, named giffonins, were isolated from the Italian cultivar “Tonda di Giffoni”. Even if many efforts have been made to establish the chemistry of these compounds, little is known about their biological properties. Herein, the inhibitory effects of diarylheptanoids isolated from C. avellana byproducts against α-glucosidase enzyme were evaluated. Molecular docking experiments disclosed the establishment of several key interactions between all the screened diarylheptanoids and the protein counterpart, whose model was built through homology modeling procedure, thus rationalizing the detected inhibitory activities. Specifically, the most active compounds giffonin J (10), K (11), and P (16) were able to make both H-bonds and π-π stacking contacts with different residues belonging to the binding site responsible for the catalytic activity of the investigated enzyme. To highlight the occurrence of the bioactive diarylheptanoids in the extracts of C. avellana byproducts obtained by eco-friendly extractions, their LC-MS profiles were analyzed. LC-MS analysis showed how giffonin J (10), K (11), and P (16) occurred in the ethanol extract of the leaves, while in the extracts of shells and green leafy involucres only giffonin P (16) was evident. Moreover, the quantitative analysis of giffonin J (10), K (11), and P (16) in C. avellana byproducts was carried out by an analytical approach based on LC-ESI/QTrap/MS, using the Multiple Reaction Monitoring (MRM) experiment. These results prompt to evaluate C. avellana byproducts, especially the leaves, as a prospective source of bioactive diarylheptanoids for the development of functional ingredients for the treatment of diabetes.